Influence of sulfur dioxide-related interactions on PM2.5 formation in iron ore sintering. (3rd April 2017) - Ji, Zhiyun; Fan, Xiaohui; Gan, Min; Chen, Xuling; Lv, Wei; Li, Qiang; Zhou, Yang; Tian, Ye; Jiang, Tao
ABSTRACT: The formation of PM2.5 (aerosol particulate matter less than 2.5 µm in aerodynamic diameter) in association with SO2 emission during sintering process has been studied by dividing the whole sintering process into six typical sampling stages. A low-pressure cascade impactor was used to collect PM2.5 by automatically segregating particulates into six sizes. It was found that strong correlation existed between the emission properties of PM2.5 and SO2 . Wet mixture layer (overwetted layer and raw mixture layer) had the function to simultaneously capture SO2 and PM2.5 during the early sintering stages, and released them back into flue gas mainly in the flue gas temperature-rising period. CaSO4 crystals constituted the main SO2 -related PM2.5 during the disappearing process of overwetted layer, which was able to form perfect individual crystals or to form particles with complex chemical compositions. Besides the existence of individual CaSO4 crystals, mixed crystals of K2 SO4 -CaSO4 in PM2.5 were also found during the first half of the temperature-rising period of flue gas. The interaction between fine-grained Ca-based fluxes, potassium vapors, and SO2 was the potential source of SO2 -related PM2.5 . Implications : The emission property of PM2.5 and SO2 throughout the sintering process exhibited well similarity. This phenomenon tightened the relationship between the formation of PM2.5 and the emission of SO2 . Through revealing the properties of SO2 -related PM2.5 during sintering process, the potential interaction between fine-grained Ca-based fluxes, potassium vapors, and SO2 was found to be the source of SO2 -related PM2.5 . This information can serve as the guidance to develop efficient techniques to control the formation and emission of PM2.5 in practical sintering plants.